The complete mitochondrial genome of the Papilio machaon annae Gistel (Lepidoptera: Papilionidae: Papilioninae). Issue 1 (2nd January 2019) - Pan, Zhongqi; Xu, Chang; Nie, Lan; Hao, Jiasheng
Abstract: The mitochondrial genome of Papilio machaon annae is described in this study. The molecule is 15, 339 bp in length and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and an AT-rich region. All PCGs use the typical start and stop codons, except COI, COII use single T–– and ND3 uses ATG as their stop codons. The rrnL and rrnS genes are 1365 bp and 780 bp in length, respectively. The AT-rich region contains several structures characteristic of the lepidopterans. Phylogenetic analysis shows that P. machaon annae is the closest realtive of Papilio hospiton, rather than the Papilio machaon .